2012
DOI: 10.1007/s12031-012-9868-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features and Molecular Analysis of Primary Glioblastomas in Moroccan Patients

Abstract: Glioblastoma is the most frequent and most aggressive primary brain tumor. Primary and secondary glioblastomas develop through different genetic pathways. The aim of this study was to determinate the genetic and clinical features of primary glioblastoma in Moroccan patients. The blood and tumor samples were obtained from a group of 34 Moroccan patients affected with primary glioblastoma. The tumors were investigated for TP53, IDH1, and IDH2 mutations using PCR sequencing analysis. Clinicopathological data show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…To date, glial tumors in Moroccan population have not been investigated, except one study involving molecular analyses of TP53 and IDH1/2 genes in 34 primary glioblastoma cases with no mutation identified in IDH1/2 genes [39]. This study is complementary to the first Moroccan study and whose results are consistent with those of international literature.…”
Section: Discussionsupporting
confidence: 68%
“…To date, glial tumors in Moroccan population have not been investigated, except one study involving molecular analyses of TP53 and IDH1/2 genes in 34 primary glioblastoma cases with no mutation identified in IDH1/2 genes [39]. This study is complementary to the first Moroccan study and whose results are consistent with those of international literature.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, younger age, good Karnofsky performance status (KPS) at the time of diagnosis, radiotherapy, histology and extent of tumor resection have been identified as potential prognostic factors for patients with GBM [5,[11][12][13][14][15][16][17][18] . In a previous study, we analyzed TP53 and IDH1-2 genes in 34 GBM cases [19] . Here we attempted to clarify the prognostic value of some clinical, therapeutic and tumor parameters noted in Moroccan GBM patients.…”
mentioning
confidence: 99%
“…It was reported in these selected articles, after sequencing of 65 and 62 patients in two different studies performed by Senhaji et al, the IDH 1 gene mutation (codons 132) was found in 12.36% and 36.75% of patients with glioblastoma (Senhaji et al, 2017, Senhaji et al, 2016). On the other hand, the study of Hilmani et al reported that there is no IDH 1 gene mutation among 34 patients with primary glioblastoma (Hilmani et al, 2013).…”
Section: Resultsmentioning
confidence: 97%
“…Loss of the p53 gene in GBM is due to mutations in exons 5 and exon 8 or homozygous/heterozygous deletion of chromosome 17 (Nagpal et al, 2006). The mutations affected exon 8 of the p53 gene are missense at R273H (818 G > A), and nonsense at R306X (916 C > T).The other mutation in exon 5 localized at Q136X (406C > T) (Hilmani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%